If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 4) + -16 = 20 Reorder the terms: 2(4 + x) + -16 = 20 (4 * 2 + x * 2) + -16 = 20 (8 + 2x) + -16 = 20 Reorder the terms: 8 + -16 + 2x = 20 Combine like terms: 8 + -16 = -8 -8 + 2x = 20 Solving -8 + 2x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 2x = 20 + 8 Combine like terms: -8 + 8 = 0 0 + 2x = 20 + 8 2x = 20 + 8 Combine like terms: 20 + 8 = 28 2x = 28 Divide each side by '2'. x = 14 Simplifying x = 14
| 1.5y+6= | | 2x+9=x^2 | | m+29=-52 | | x-48=-47 | | 7x-3+11x+3=162 | | 3kx^2-2kx+1=0 | | 3.6=r-2.3 | | -4x+6=2x+18 | | a^2-8=26 | | 8.2x+4=7.6x+10 | | x+3=-x-6 | | 64=-2r | | 8.2+4=7.6x+10 | | 9x^2=6-4x | | q+6whenq=12 | | 1-3/5+1/2= | | 2x^2-190x+2400=0 | | 0.50x+0.15(30)=46.5 | | -9c-5=13 | | z-7=14 | | -7=m(-6)+b | | 42+m=-21 | | -36+f=4 | | -2+3x=4x-7-x | | -1/2(6x+9)-(x-3/2)= | | 2+x=-(x+6) | | 2(13x-15)+3(x-19)=0 | | 2x+5+3x=15 | | h+4=-3 | | -4(3y-6)-y=-3(y-4) | | 2x^2-22x+28.5=0 | | 16+z=14 |